Jatropha curcas poisoning in a family from rural Haryana - Sangeeta Choudhary; Surbhi Gupta; Nidhi Sharma (Wolters Kluwer Medknow Publications, 2022)
Background: Jatropha curcas is a flowering plant found all over the world. It has traditionally been used for medicinal purposes and as an ornamental plant. Lately, it is being promoted for biodiesel production. Since it is a commonly grown plant with seeds that are often mistaken as edible nuts, accidental ingestion is common among children. The presence of various plant toxins results in gastrointestinal, hepatic renal cardiotoxic, and hemolytic manifestations. The general public and most pediatricians are unaware of this. Clinical Description: We report a case series of thirteen children who presented to the emergency department with lethargy, abdominal pain, vomiting, and diarrhea after acute ingestion of seeds of an unknown plant. The presentation varied in severity of symptoms as well as degree of dehydration, which seemed to correspond to the number of seeds consumed. The parents were asked to bring parts of the plant and the seeds were identified to belong to the Jatropha curcas plant after expert botanical consultation. Management and Outcome: All the children were admitted. None of them had manifestations of any specific toxidrome, however, there seemed to be isolated gastrointestinal involvement, clinically. Gastric lavage was done immediately. Intravenous fluid correction was administered based on the severity of dehydration. Supportive treatment with antiemetics and antacids was provided. Baseline investigations were planned to rule out organ dysfunction. The most common derangement was neutrophilic leukocytosis. All children recovered well without any complications or sequelae. Conclusion: Jatropha Curcas is a noxious plant that should not be grown in areas where children play. Unknown plant poisoning should be treated with the same gravity as any other poisonous substance. All efforts should be taken to look for indicators of a specific toxidrome in case an antidote is warranted, as well as identify the concerned plant.